Tendencies of Legal Regulation of Socio-Economic Relations in Construction in Developed Democracies - Marusheva, Oleksandra (Pressing Problems of Public Administration, 2019)
The article presents analysis of particular characteristics of functioning of the legal regulation mechanism for socio-economic relations in construction. It is substantiated that the government authorities in developed democracies in this important  eld exist in different forms: in the form of several government organizations, a single executive body (ministry) in construction, or respective departments within the integrated ministries (of ecology, regional policy, transport, infrastructure and housing and communal services, etc.). It is noted that such system is centralized in Germany, and, besides federal agencies, as well as land authorities, it includes local self-government, which, along with other issues, also deals with construction. It is noted that the mechanism of government regulation of socio- economic relations in construction in developed democracies is implemented both at the national level and with the help of professional self-regulation and independent experts in this  eld. For instance, in France, the architectural and construction control system has a hybrid character. It is noted that the experience of organizing and implementing architectural and construction control in developed democracies is a necessary basis for improving the national system of government architectural and construction control. The international practice regarding participation of independent private specialized bodies and agencies or individual experts in exercising control functions would not only improve the quality of control measures, but also reduce the level of corruption in the city planning sphere.